1995
DOI: 10.1063/1.114656
|View full text |Cite
|
Sign up to set email alerts
|

Intensity dependent mode competition in second harmonic generation in multimode waveguides

Abstract: Temperature dependence and single-mode tuning behavior of second-harmonic generation in quantum cascade lasers Appl.Device length dependence of optical second-harmonic generation in AlGaAs quasiphase matched waveguides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Nevertheless, for sufficiently high laser intensities strongly pronounced nonlinear effects due to cascading have also been observed for finite phase mismatches [19,32]. Experimentally it was also demonstrated that the fundamental FW00 mode can interact with several SH modes simultaneously [33] and that this leads to nonlinear competition and suppression of spatial nonlinear effects in WGAs [28]. Here we study such a system with two competing nonlinear interactions.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Nevertheless, for sufficiently high laser intensities strongly pronounced nonlinear effects due to cascading have also been observed for finite phase mismatches [19,32]. Experimentally it was also demonstrated that the fundamental FW00 mode can interact with several SH modes simultaneously [33] and that this leads to nonlinear competition and suppression of spatial nonlinear effects in WGAs [28]. Here we study such a system with two competing nonlinear interactions.…”
Section: Introductionmentioning
confidence: 88%
“…For weak linear and nonlinear coupling strengths light propagation in the investigated discrete system can be described by the following normalized coupled mode equations [22,33]:…”
Section: Basic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the same wavelength range the phase mismatch Δβ 2 between FW00 and SH10 mode [see mode profile in Fig. 1(a)] becomes small [29,30], leading to efficient nonlinear interaction. Hence in our analysis we have to consider a system featuring all the coupling mechanisms shown in Fig.…”
Section: Spatial Cw Soliton Phase Transition With Two Sh Modesmentioning
confidence: 99%
“…1(d) shows a scheme of the three bands governing the propagation of the modes taken into account here. The nonlinear propagation of cw-waves in the lithium niobate WGA, taking into account one FW and two SH modes, can be described with the following coupled mode equations for the mode amplitudes in the waveguides [29,31]:…”
Section: Spatial Cw Soliton Phase Transition With Two Sh Modesmentioning
confidence: 99%